Unusual pregnancy in the rudimentary horn of the uterus - Shetty, Anusha S.; Tondge, Ganesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mullerian anomalies are rare to be diagnosed, most of the females with Mullerian anomalies go undiagnosed, as they remain asymptomatic. It is a rare clinical scenario that surprises clinicians since it poses difficulty in diagnosis and treatment. Hereby, we describe a case of a 24-year-old, gravid-2-abortion-1 woman who complained of increased abdominal pain and vaginal bleeding with 9 weeks pregnancy. During past laparoscopic surgeries, she was diagnosed of having a bicornuate-uterus. The first sonography reported a bicornuate uterus with a missed-abortion of 9 weeks. As she was taken up for suction-evacuation, suspicion of a unicornuate-uterus with rudimentary horn raised as no products of conception were evacuated. Repeat ultrasound and MRI demonstrated a gestation sac in the non-communicating rudimentary horn attached to the unicornuate uterus. Further diagnostic hysteroscopy and laparoscopy confirmed the diagnosis of pregnancy in the non-communicating rudimentary horn of the unicornuate uterus with a right-sided ovarian cyst not separately seen from the right-sided fallopian tube and ovary for which the decision of laparoscopic resection of the rudimentary horn and right salpingo-oophorectomy was made. Patient was later discharged without any complications and was advised contraception for the next 6-12 months. Further consultations for infertility and urinary tract abnormalities were organized. Though rare, cases of Mullerian anomalies need to be addressed with utmost care because usually they might present with symptoms of pain or infertility, but rarely they might have catastrophic consequences such as rupture of the rudimentary horn. Hence, prompt diagnosis and management are necessary.